DISTRIBUSI SPASIAL HOT SPOT DAN SEBARAN ASAP INDIKATOR KEBAKARAN HUTAN/LAHAN DI PULAU SUMATERA DAN KALIMANTAN TAHUN 2002 - Any Zubaidah; Muchlisin Arief (Indonesian National Institute of Aeronautics and Space (LAPAN), 2004)
Forest/land fire in Indonesia occurs almost every year. Itis merely due to natural factor, but due to human's activity as well like in opening of new land for agriculture purpose or plantation, or forming of land/land clearing. Fire that is indicated by the existenceof hot spot can be monitored daily using near infra-red channel and thermal (channel 3 and 4) from NOAA-AVHRR satellite data (National Oceanic and Atmospheric Radiometer-Advanced Very High Resolution Radiometer). Pursuant to the daily hot spot monitoring in Sumatera in the year 2002, forest/land fire has occurred since January until December, while in Kalimantan, it start in March until December. The fluctuation of hot spot in the year 2002 has almost the same pattern with the year 1997's, where the peak of fire occurred in September in Kalimantan Island and in October in Sumatera Island. Besides, pursuant to NOOA and Feng Yun data, haze distribution that occurred in the year 2002 was not too significant and haze distributions that mostly took place in September in Kalimantan and in October in Sumatera. Degradation of fire activity occurs in the following month where the fire in the two island drop along with the increasing of rainfall in the two island.